(untitled) (jornal of the libyan geographical society, 2016)
The advancement and development of nations depends on the educated elite among their people, as they reflect positive effects on their society, due to their ability to acquire modern knowledge and technologies and their possession of a spirit of initiative and innovation, which makes them enjoy a level of awareness that helps them to make the right decisions more than the less educated groups. It also enables it to contribute effectively to improving production and boosting economic growth. Currently, studies concerned with developing competencies and human resources have garnered the attention of many specialists and analysts. Competence refers to the set of characteristics that an individual possesses or acquires, such as knowledge, skills, and attitudes, enabling them to perform specific tasks within a particular field. A competent person is defined as someone who possesses the knowledge and skills necessary to perform a task or job at the required level. Higher education institutions are considered to be such institutions. One of the most important means of assisting in the formation of scientific and technical competencies is teachers, researchers, administrators, engineers, doctors and others who form the basic elements of the intellectual and scientific foundation of society, on which progress and development depend.